Effect of Hibiscus sabdariffa (Calyce) Extract on Biochemical and Organoleptic Properties of Yogurt - Iwalokun, B.A.; Shittu, M.O. (Pakistan Journal of Nutrition, 2007)
Previous studies have shown that substances incorporated into milk before and after fermentation elicit profound influence on the physicochemical properties of yogurt and consumers` sensory perception of their acceptability as healthy and refreshing drinks. This study examined the effect of Hibiscus sabdariffa calyx extract on pH, titratable acidity (TA), syneresis, ash and moisture contents in two brands of low fat milk (LFM) yogurts when incorporated before and after fermentation. Results were compared to those of plain and strawberry yogurts with the sensory profiles of the yogurts after manufacture and on days 3, 5 and 7 of storage under refrigeration temperature (8±1°C) determined and compared on a 9 point-hedonic scale using 10 independent yogurt accustomed panelists. Incorporation of Hibiscus sabdariffa calyx extract into the reconstituted LFM (500g) resulted in significant (P < 0.05) decreases in coagulation time 5.5±0.4 vs. 6.2±0.8 h), pH 4.4-4.16 vs. 4.54-4.31± (0.003-0.007), syneresis 0.8-1.9 vs. 1.3-2.6 ± (0.01-0.04) and galactosodase activity (1.02-1.86 vs. 0.57-0.98±0.02-0.05 U/g) after manufacture and during storage. Microbial analysis revealed the presence of non-starter isolates: L. plantarum, L. brevis and higher total LAB count (2.5-3.1 x 10 9 vs. 1.2-1.5 x 10 7 cfu/ml; P < 0.05) on day 7 in the sabdariffa yogurts. Sensory evaluation recorded significantly (P < 0.05) lower scores on aroma (2.6-4.1 vs. 5.3-7.7), taste (2.7-4.7 vs. 6.1-7.7), and overall acceptability (4.1-5.9 vs. 6.4-8.4) for the sabdariffa yogurts after manufacture and during storage. On the whole, the strawberry and sabdariffa (pre-added) yogurts were the most and the least preferred with retention of freshness on day 7 of storage at 8±1°C. Results indicate the need to improve on the sensory attributes of the more probiotic sabdariffa yogurts in order to optimize consumer`s perception on their acceptability.